PENGARUH RASIO CAMEL (CAPITAL, ASSET, MANAJEMEN, EARNING, LIQUIDITY) DAN ECONOMIC VALUE ADDED (EVA) TERHADAP RETURN SAHAM PERBANKAN SWASTA NASIONAL DI BEI TAHUN 2009-2013 - Fitrianti Fitrianti; Makhdalena Makhdalena; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was conducted to examine the effect of the CAMEL(Capital, Asset, Manajemen, Earning, Liquidity) Ratio and Economic Value Added (EVA) to stock return. Population of this research are National Private Banks (BUSN) that listed on the Stock Exchange of Indonesia from 2009–2013 that is numbered 19 banks. The type of data used is quantitative data. Data analysis technique using multiple linear analysis, simultan test and parsial test with significance level of 0.05%. The result showed that the CAMEL Ratio and Economic Value Added (EVA) simultaneously affect to stock return. Predictive ability of both variables on stock return in this study only 31,3 %, while the remaining 68,7 % is affected by other factors not included in the model reseach. Furthermore, the partial results of the study show the CAR, ROE, LDR, EVA have signifikan effect to stock return . NPL and BOPO have effect but not signifikan to stock return. And ROA have negatif effect and not signifikan to stock return.Keywords:CAMEL Ratio, Economic Value Added (EVA), Return Saham